Die große Vormundschaftsreform - 16. Göttinger Workshop zum Familienrecht 2018 - Coester-Waltjen, Dagmar (Universitätsverlag Göttingen, 2019)
This volume brings together the presentations of the 16th Göttingen Workshop on Family Law held on 19 October 2018, which dealt with the latest proposals of the Federal Ministry of Justice and Consumer Protection on the reform of guardianship law (2nd draft discussion section). At the beginning, the main changes were presented (Thomas Meyer, Heike Wunderlich) before the basic concept of guardianship responsibility in the area of personal care was examined from the perspective of science (Dieter Schwab), child and youth welfare (Helga Oberloskamp) and family jurisdiction (Werner Dürbeck). This was followed by a closer look at the basic principles of the guardian's asset care (Tobias Fröschle) as well as the guardian's obligation to obtain approval for dispositions of claims and securities (Dagmar Zorn).